Jackie Chan : action collection [videorecording (DVD)]. - Cheng, Long, 1954-; Cheng, Long, 1954-; Cheng, Long, 1954-; Wang, Xingdong; Huang, Wei; Lin, Chaoyang; Ding, Wei; Chen, Minzheng; Chao, Winston; Li, Bingbing, 1976-; Sun, Chun, 1956-; Chen, Joan, 1961-; et al. (Well Go USA Entertainment, 2023)
1911 revolution: A historical action war drama based on the founding of the Republic of China, when nationalist forces led by Sun Yat-sen overthrew the last ruling Qing Dynasty, which held unquestioned power and rule for 250 years. From the walls of the Forbidden City to the battlefields of China, no expense was spared in the production and no detail ignored in its quest for historical accuracy. 1911 is a true epic to be enjoyed for generations.